THE CONDITIONING EFFECT OF TIME ON FIRM SURVIVAL: AN INDUSTRY LIFE CYCLE APPROACH. - Agarwal, R.; Sarkar, M. B.; Echambadi, R. (Academy of Management Journal, 2002)
Man effort to reconcile theoretical "blind spots," we integrated research in technology management, organizational ecology, and evolutionary economics. The central premise underlying the resultant model is that time conditions the effects of age, contemporaneous size, order of entry, and contemporaneous density on mortality rates. We tested our hypotheses using a life cycle approach and data on 33 product innovations that span most of the 20th century. Results resoundingly support our central thesis on the impact of time on both survival rates and relationships previously thought to be universalistic.